PENINGKATAN KETERAMPILAN BERBAHASA SISWA MELALUI PEMANFAATAN MEDIA TEKA-TEKI SILANG: MENCIPTAKAN KELAS YANG MENYENANGKAN - Syofiani Syofiani; M Zaim; Syahrul Ramadhan; Agustina Agustina (Ta'dib, 2018)
This article contains a study about the use of crossword media in improving the language skills of elementary school students as an effort to create a fun class. The problem was students’ lack of eagerness to emotionally involve in learning process. This condition caused an impact on students’ unsatisfaying learning outcomes that is 80. To overcome this problem, crossword puzzle media are used in learning by referring to the research models of Kemmis and Taggart. The data were collected by using observation sheets, interview guidelines, questionnaires, tests of student learning outcomes and field observations. At the end of the study, it was found that both the students’ learning outcomes and activities, and the teacher performance in planning and implementing teaching increased from cycle I to cycle II. As the result, the learning exceeded the target of the minimum standard of completeness. Thus, the utilization of crossword puzzles is considered to able to improve students' language skills, as well as create fun classes